Structural and Immunochemical Studies of the Lipopolysaccharide from the Fish Pathogen, Aeromonas bestiarum Strain K296, Serotype O18 - Otto Holst; Adam Choma; Agnieszka Pekala; Alicja Kozinska; Iwona Komaniecka; Anna Turska-Szewczuk; Buko Lindner (Marine Drugs, 2013)
Chemical analyses and mass spectrometry were used to study the structure of the lipopolysaccharide (LPS) isolated from Aeromonas bestiarum strain K296, serotype O18. ESI-MS revealed that the most abundant A. bestiarum LPS glycoforms have a hexa-acylated or tetra-acylated lipid A with conserved architecture of the backbone, consisting of a 1,4′-bisphosphorylated β-(1→6)-linked d-GlcN disaccharide with an AraN residue as a non-stoichiometric substituent and a core oligosaccharide composed of Kdo1Hep6Hex1HexN1P1. 1D and 2D NMR spectroscopy revealed that the O-specific polysaccharide (OPS) of A. bestiarum K296 consists of a branched tetrasaccharide repeating unit containing two 6-deoxy-l-talose (6dTalp), one Manp and one GalpNAc residues; thus, it is similar to that of the OPS of A. hydrophila AH-3 (serotype O34) in both the sugar composition and the glycosylation pattern. Moreover, 3-substituted 6dTalp was 2-O-acetylated and additional O-acetyl groups were identified at O-2 and O-4 (or O-3) positions of the terminal 6dTalp. Western blots with polyclonal rabbit sera showed that serotypes O18 and O34 share some epitopes in the LPS. The very weak reaction of the anti-O34 serum with the O-deacylated LPS of A. bestiarum K296 might have been due to the different O-acetylation pattern of the terminal 6dTalp. The latter suggestion was further confirmed by NMR.